HUBUNGAN PENERAPAN KOMUNIKASI SITUATION BACKGROUND ASSESMENT DAN RECOMMENDATION DENGAN INSIDEN KESELAMATAN PASIEN - Retno Andriati; Ayu Rahayu; Marsondang Situmeang; Dyna Meilolita Sirait; Cucum Rosmala; Oktavia Purnamasari; Team Perawat Lt 3 gd 1 (Nusantara Hasana Journal, 2026)
Introduction: One of the main causes of risk for patients is communication failure. During nursing handovers, the SBAR method can help nurses know what to convey when speaking. Research objective: to determine the relationship between SBAR communication and patient safety incidents in the Mayapada Hospital Tangerang Inpatient Room. Research method: This study used a cross sectional design. The population in this research were all nurses who cared for patients and the selected sample was 56 respondents. Statistical tests use the Chi-square test using the SPSS program. Research results: Most of the nurses who work in the Inpatient Room are female (71%), aged 20-35 (54%), have a D3 education (71%) and have worked for more than 5 years (68%). The majority of nurses had good SBAR communication (63%) and did not experience patient safety incidents (62%) in the Inpatient Room on Floor 3 of Mayapada Hospital Tangerang. Conclusion:There is a relationship between the implementation of SBAR communication by nurses and patient safety incidents in the Mayapada Hospital Tangerang Inpatient Room with a Pvalue of 0.026. It is hoped that the results of this research can provide input to nursing about the importance of patient safety in providing professional health services.